Bilateral Laplace–Feynman transforms on abstract Wiener spaces. Issue 7 (3rd July 2022) - Choi, Jae Gil
ABSTRACT: In this paper, an extension of the bilateral Laplace transform on infinite-dimensional Banach spaces is introduced. In order to develop the concept of an analytic bilateral Laplace–Feynman transform (BLFT) of functionals on abstract Wiener spaces, we complete the following objectives: we first establish the existence of the analytic BLFT of certain bounded functionals on B . We next extend the operational properties (shifting properties) of the bilateral Laplace transform of functions on Euclidean spaces to the cases of the BLFT of functionals on abstract Wiener spaces. We also provide a convolution product (CP) corresponding to the BLFT and establish a relationship between the BLFT and the CP. We finally provide a representation of an inverse transform of the BLFT. Specifically, we establish a representation of the inverse transform for the BLFT having special parameter via the concept of the analytic Fourier–Feynman transform (FFT).